2016
DOI: 10.1177/2333393616681935
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Trust in Successful Home Visit Programs for Older People

Abstract: Outcomes of proactive home visit programs for frail, older people might be influenced by aspects of the caregiver–receiver interaction. We conducted a naturalistic case study to explore the interactional process between a nurse and an older woman during two home visits. Using an ethics of care, we posit that a trusting relationship is pivotal for older people to accept care that is proactively offered to them. Trust can be build when nurses meet the relational needs of older people. Nurses can achieve insight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Feeling supported by and experiencing a better relationship with the care provider has also been reported in other coordinated care interventions (Baxter & Markle‐Reid, ; Metzelthin, Daniels, et al, ; Poot, Caljouw, Waard, Wind, & Gussekloo, ). Trust appears to be the foundation of the relationship between care provider and older person and has an impact on the acceptance of offered care (Bindels, Cox, Widdershoven, van Schayck, & Abma, ; van Kempen et al, ; Muntinga et al, ). Also, in our study, mistrust among older persons towards unfamiliar services and care providers was a main barrier towards participation in care.…”
Section: Discussionmentioning
confidence: 99%
“…Feeling supported by and experiencing a better relationship with the care provider has also been reported in other coordinated care interventions (Baxter & Markle‐Reid, ; Metzelthin, Daniels, et al, ; Poot, Caljouw, Waard, Wind, & Gussekloo, ). Trust appears to be the foundation of the relationship between care provider and older person and has an impact on the acceptance of offered care (Bindels, Cox, Widdershoven, van Schayck, & Abma, ; van Kempen et al, ; Muntinga et al, ). Also, in our study, mistrust among older persons towards unfamiliar services and care providers was a main barrier towards participation in care.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to provide person-centered care based on individual needs in order to gain the trust of the patients. Person-centered care is considered the best practice care for geriatric patients with multiple conditions and requires interprofessional collaboration due to different health care providers and the involvement of family caregivers [20,21]. A few studies have shown that the satisfaction of patients and their quality of life has improved, which was mainly reported by the patients themselves [12,22,23].…”
Section: Introductionmentioning
confidence: 99%